2016
DOI: 10.1016/j.brainres.2016.01.048
|View full text |Cite
|
Sign up to set email alerts
|

Altered hypothalamic inflammatory gene expression correlates with heat stroke severity in a conscious rodent model

Abstract: It has been suggested that heat-induced hypothalamic damage mediates core temperature (Tc) disturbances during heat stroke (HS) recovery; this is significant as hypothermia and/or fever have been linked to severity and overall pathological insult. However, to date there has been a lack of histological evidence in support of these claims. We hypothesized that local hypothalamic cytokines and/or chemokines, known regulators of Tc, are mediating the elevation in Tc during HS recovery even in the absence of histol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…Across different species, heat acclimation has been shown to protect against a wide range of stressors ( Shein et al, 2008 ; Umschwief et al, 2010 , Umschweif et al, 2014 ; Assayag et al, 2012 ; Horowitz, 2017 ; Pollak et al, 2017 ; Hossain et al, 2018 ). Various findings point to the hypothalamus as the site of convergence of thermal–inflammation-related networks ( Tzschentke, 2007 ; Tona et al, 2008 ; Tzschentke and Halle, 2009 ; Hueston and Deak, 2014 ; Loyau et al, 2014 , 2016 ; Chao et al, 2015 ; Klett et al, 2015 ; Nassar et al, 2015 ; Audet et al, 2016 ; Morrison, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Across different species, heat acclimation has been shown to protect against a wide range of stressors ( Shein et al, 2008 ; Umschwief et al, 2010 , Umschweif et al, 2014 ; Assayag et al, 2012 ; Horowitz, 2017 ; Pollak et al, 2017 ; Hossain et al, 2018 ). Various findings point to the hypothalamus as the site of convergence of thermal–inflammation-related networks ( Tzschentke, 2007 ; Tona et al, 2008 ; Tzschentke and Halle, 2009 ; Hueston and Deak, 2014 ; Loyau et al, 2014 , 2016 ; Chao et al, 2015 ; Klett et al, 2015 ; Nassar et al, 2015 ; Audet et al, 2016 ; Morrison, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…We have presented in this work, to our knowledge, the first RNAseq analysis of tissue from an animal model of heat stroke. While other studies have presented gene expression assayed by quantitative PCR [27][28][29] , the advantage of RNAseq is the agnostic measure of the full transcriptome, rather than a set of pre-chosen RNAs. This agnostic search allows us to assay a greater extent of perturbation to the system state of the tissue, without narrowing our view with expectations.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of pathology, chemokines and chemokine receptors are involved in many CNS disorders, including Alzheimer's disease, Parkinson's disease, multiple sclerosis, and amyotrophic lateral sclerosis [28]. A previous study revealed significant changes in the expression of 25 cytokines and chemokines in the hypothalamus of heat-stroke rats [3]. Our results showed that these changes may occur in astrocytes, rather than neurons, so the former may thereby contribute to neuroinflammation and aggravate neural injury.…”
Section: Discussionmentioning
confidence: 46%
“…It was surprising that C6, Ccl3, and Ccr1 were all up-regulated in RNA-seq and qPCR in primary astrocyte culture after heat stress, but down-regulated in heat-stroke rats. According to previous work on whole hypothalamic tissue, the transcriptional levels of CCL3 and CCR1 are down-regulated in heat-stroke rats [3]. In addition, down-regulation of C5, CCL12, CCL4, and CCR3 was found, while CCL6, CCR8, and CXCL13 were up-regulated.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation